Hard country : a thriller - Wortham, Reavis Z. (Poisoned Pen Press, 2023)
"There is no peace in the hard country Tucker Snow is as tough as they come, hardened by decades working as an undercover narcotics agent for the Texas Department of Public Safety. Through special dispensation from the governor, he and his brother Harley cut a wide swath through the criminal element of Northeast Texas. But tragedy comes calling after taking a dream job as a special ranger with the Texas and Southwestern Cattle Raisers Association, when Tucker's wife and toddler are killed in a horrific traffic accident caused by a drug addled felon. Close to breaking, Tucker sets his badge aside to move his surviving teenage daughter outside of Ganther Bluff, a quiet town with enough room for them to mourn their unexpected loss. But peace doesn't last long for a man like Tucker Snow. Instead of settling into small-town life to heal from such an unimaginable loss, a fresh kind of hell hits them with full force. Crimes and secrets strangle this rural community, and when a new form of meth with the street name of gravel gets too close to home, it's enough for Tucker to put his badge back on and call Harley for help. The town will ultimately be better off with him as a resident lawman, but this unforgiving landscape will threaten everything Tucker holds dear"--